2018
DOI: 10.1007/s10151-018-1830-1
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with rectal prolapse: the 2017 Dutch guidelines

Abstract: These guidelines for clinical practice are useful in the diagnosis and treatment of rectal prolapse. There are many statements requiring a higher level of evidence due to a lack of studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 56 publications
1
42
0
1
Order By: Relevance
“…7 New guidelines also recommend laparoscopic or minimally abdominal approaches for rectal prolapse surgery. [1][2][3] In this issue, a retrospective study of the surgical treatment of rectal prolapse also showed this changing trend of surgical management. 8 Although the number of patients is not enough to make any solid conclusions, among 18 abdominal approaches, laparoscopic approaches comprised 16 operations (88.9%).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…7 New guidelines also recommend laparoscopic or minimally abdominal approaches for rectal prolapse surgery. [1][2][3] In this issue, a retrospective study of the surgical treatment of rectal prolapse also showed this changing trend of surgical management. 8 Although the number of patients is not enough to make any solid conclusions, among 18 abdominal approaches, laparoscopic approaches comprised 16 operations (88.9%).…”
mentioning
confidence: 89%
“…Many published guidelines recommend a perineal approach for unhealthy patients with general anesthesia or abdominal procedures. [1][2][3] On the other hand, with the improvement of perioperative care, the absolute contraindication to general anesthesia is decreased markedly.…”
mentioning
confidence: 99%
“…5 The high rate of spontaneous resolution differentiates pediatric rectal prolapse from adult prolapse where resolu-tion is unexpected without intervention. [6][7][8] The difference is especially true in children less than 4 years of age who are otherwise healthy. 2,6,9 Given the high rate of resolution, the number of children who ultimately undergo surgical intervention is low.…”
Section: Introductionmentioning
confidence: 99%
“…It can be divided into external rectal prolapse and internal rectal prolapse or rectal intussusception. [ 1 ] The incidence of rectal prolapse is not high and is estimated to occur in less than 0.5% of the population. [ 2 ] Rectal prolapse occurs at the extremes of age, [ 3 ] of which the frequency is higher in children, the elderly, and females.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Rectal prolapse occurs at the extremes of age, [ 3 ] of which the frequency is higher in children, the elderly, and females. The age of incidence for children is generally before 4-year-old, [ 4 ] for the elderly is generally after 50-year-old, the proportion of females is higher than that of men (ratio 9:1), [ 1 ] and the higher incidence occurs with the older age. [ 5 ] The clinical manifestations include pain, bleeding, and fecal incontinence.…”
Section: Introductionmentioning
confidence: 99%